Chính sách tài khóa và kiểm soát ô nhiễm từ khí thải CO2: Nghiên cứu trường hợp các nước đang phát triển - Sử Đình , Thành; Nguyễn Văn , Bổn (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
The results of investigations into the relationship between fiscal policy and CO2 emissions are still a matter for debate. This paper empirically estimates the effects of fiscal policy on CO2 emissions through a panel of 60 developing countries over the period of 2001–2014. This study also takes account of the commitments of governments in developing countries to implement the Kyoto Protocol. The fiscal policy is proxied by such three variables as public spending, tax revenue, and fiscal deficit. The estimated results of GMM system estimator show that: (i) The effects of three fiscal variables on CO2 emissions are significantly negative; (ii) Since governments in developing countries committed to implement the Kyoto Protocol, the influences of the three fiscal variables have been significantly negative.
Keywords: Fiscal policy; CO2 emissions; Developing countries; GMM system